LITERASI DIGITAL BAGI PELAJAR: BIJAK BERMEDIA SOSIAL DAN CERDAS MEMANFAATKAN MEDIA MASSA (STUDI KASUS KONTEN MAKANAN DI SMK MERAH PUTIH BEKASI) - Ari Kurnia; Laras Cempaka (Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
The mass media is an important role in the development of information. Also, social media has now become a reference for someone looking for more concise and interesting information. This is the style of media consumption by society, especially young people in Indonesia. As students at SMK Merah Putih Bekasi, students still lack information on how to manage mass media properly and according to their needs. Interesting content is considered as content that can entertain and motivate someone to be like what is seen on social media. The purpose of this service is to educate students in sorting out the right information and not being careless in applying it in everyday life, especially in trusting food content. This content is considered to still provide an unbalanced understanding of a person's nutritional needs. Based on the guidelines for balanced nutrition, education was distributed under the theme Isi Piringku. Through the case study method, participants admitted they did not understand how the social media system works and the "rules of the game" for consuming mass media. The educational method is counseling, then the practice of checking text data for each content on mass media and social media using the website https://turnbackhoax.id and/ or Google Fact Check Tools, honing skills in consuming food according to the contents of Isi Piringku. In general, respondents had heard of the term Isi Piringku, but did not fully understand the concept based on Balanced Nutrition. In terms of attitude and practice, it can be said that not many of the recommendations for balanced nutrition have been implemented. Through counseling activities, students gain an understanding of proper nutrition for their daily intake needs and are supplemented by the Isi Piringku simulation process. It is hoped that an understanding of social media and mass media, as well as an understanding of nutritional information will enable students to sort out the foods they can consume daily